La “città delle barricate”. Funzioni e significati delle barricate a Barcellona in un secolo di sommosse (1835-1937) (Spagna contemporanea. Rivista semestrale di storia, cultura, istituzioni, 1996)
The “Town of the barricades”. Functions and meanings of Barcelona’s barricades during a century of popular uprisings (1835-1937).During the Nineteenth century and in the first half of the Twentieth Barcelona has witnessed many popular conflicts accompanied by the raising of barricades in the town’s streets. The frequency of such an event denies its dependence from a unique ideological and politicai source, whilst emphasising a special inclination — within that typical social layer — towards the expression of different contents through the barricades. The essay then, focusing on some specific Barcelonese uprisings, studies — besides the traditional military functions of the barricade — also the ones aimed at fractioning the urban space in order to re-create the small community and, at the same time, to destroy the “town of the others”, the popular classes’ “enemy town”.